NORMATIVE RECONSTRUCTION IN CONSTITUTIONAL COURT DECISIONS - Imam Al Ghozali (Acceleration: Multidisciplinary Research Journal, 2023)
Decision Supreme Court Constitution (MK) against application judicial review is declaratory which is not own power executive. Because of that considered No ensure exists certainty and benefit law. Study This aim reconstruct norm law for judgment declaratory the own Power constitutional in a manner whole . Study juridical normative, with critical statute approach , research This recommend amendments to the 1945 Constitution Article 24 C and amendments to Law Number 24 of 2003, Law Number 12 of 2011 Article 7 paragraph (1) to position Decision Judicial Review MK became norm law written.